Training of behavior-analytic therapists: supervisor behaviors - Contarin, Lara Sorita [UNESP]; Spasiani, Gabriela Vanzo [UNESP]; Jacinto, Helyson Fernando de Aguiar [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2023)
The research developed on the training of therapists in Analytical-Behavioral Therapy makes little explicit about clinical supervision strategies, during training in Psychology, so that there is acquisition of repertoire to deal with cases of comorbid anxiety and depression. This article presents an excerpt from a single-subject design whose objective was to describe a process of supervision of novice therapists who assisted two clients with successful results regarding the reduction of symptoms of anxiety and depression and the acquisition of skillful behaviors. Recordings of the care provided and also of the supervision sessions were used. After listening to the recordings, the supervisor’s behaviors were categorized and accounted for, using a protocol previously developed. The results obtained revealed regularity in the behavior of the internship supervisor, as there were statistically significant differences in the same categories for both therapists. Likewise, there was flexibility according to the demands and needs of each therapist and client. It was also possible to observe similarities between the practice of internship supervision and the therapist-client relationship. Future research will be able to use the protocol developed to evaluate its generalization for Analytical-Behavioral Therapy, as well as using video sessions to be able to capture more nuances of interactions.
Formação de terapeutas analítico-comportamentais: comportamentos do supervisor
Keywords: behavior-analytic therapy; behavioral clinic; internship supervision; supervisor behaviors; therapist training